2017
DOI: 10.1016/j.drugpo.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Addiction stigma and the biopolitics of liberal modernity: A qualitative analysis

Abstract: Definitions of addiction have never been more hotly contested. The advance of neuroscientific accounts has not only placed into public awareness a highly controversial explanatory approach, it has also shed new light on the absence of agreement among the many experts who contest it. Proponents argue that calling addiction a 'brain disease' is important because it is destigmatising. Many critics of the neuroscientific approach also agree on this point. Considered from the point of view of the sociology of healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
122
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 37 publications
1
122
0
3
Order By: Relevance
“…Proponents of the BDMA argue that it will benefit addicted individuals by reducing moral judgment and providing enhanced biomedical interventions (e.g. However, critics have contested the neurobiological evidence underpinning the BDMA, claiming it may increase stigma for people with addictions and lead policy makers to focus on medical solutions to social problems [5][6][7][8][9]. However, critics have contested the neurobiological evidence underpinning the BDMA, claiming it may increase stigma for people with addictions and lead policy makers to focus on medical solutions to social problems [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Proponents of the BDMA argue that it will benefit addicted individuals by reducing moral judgment and providing enhanced biomedical interventions (e.g. However, critics have contested the neurobiological evidence underpinning the BDMA, claiming it may increase stigma for people with addictions and lead policy makers to focus on medical solutions to social problems [5][6][7][8][9]. However, critics have contested the neurobiological evidence underpinning the BDMA, claiming it may increase stigma for people with addictions and lead policy makers to focus on medical solutions to social problems [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Substance dependent individuals define their feelings as being treated by health care professionals in a different way compared to other patients and as being belittled. These individuals experiencing labeling anxieties with past experiences do not go to hospital even when they have minor health problems and are unable to prevent these problems from turning into more difficult and serious situations later (Fraser et al, 2017).…”
Section: Stigma That Substance Abusers Individuals Facementioning
confidence: 99%
“…Fraser et al (2017 identified in their study that substance dependent individuals are exposed to labeling in the health care system, in their offices, in judiciary systems, in media, family and friend environments (Fraser et al, 2017). Kelly et al (2009) expressed in their study that depending on the labeling they are exposed http://dx.doi.org/10.15405/epsbs.2017.09.23 Corresponding Author: Z. Yaman Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 252 to, substance using individuals have difficulties in setting up a home, in their offices and in getting health care and that they are judged and denied by health care professionals (Kelly and Westerhoff, 2009).…”
Section: Stigma That Substance Abusers Individuals Facementioning
confidence: 99%
See 1 more Smart Citation
“…De hecho, desde la perspectiva de la sociología de la salud y la enfermedad, la idea de que el hecho de etiquetar algo como enfermedad mitigará el estigma no deja de ser sorprendente (Fraser et al, 2017).…”
unclassified